A sustainable waterborne vanillin–eugenol–acrylate miniemulsion with suitable antibacterial properties as a substitute for the styrene–acrylate emulsion. Issue 19 (13th September 2021) - Zhang, Lei; Ma, Jianzhong; Lyu, Bin; Zhang, Yuehong; Thakur, Vijay Kumar; Liu, Chenyang
Abstract : Sustainable monomers DV and DE were employed as substitutes for styrene and a petroleum-based crosslinker respectively to copolymerize with BA to afford a waterborne P(DV–BA–DE) miniemulsion, which is an ideal antibacterial coating for leather. Abstract : In this work, we have performed a solvent-free, facile synthesis of renewable aromatic monomers, double bond modified vanillin (DV) and double bond modified eugenol (DE). The resulting DV and DE were respectively used as sustainable alternatives for petroleum-based styrene (St) and the diacetone acrylamide–adipic acid dihydrazide (DAAM–ADH) crosslinker to copolymerize with butyl acrylate (BA) to prepare a sustainable, water-borne P(DV–BA–DE) miniemulsion by the miniemulsion polymerization technique. The monomer conversion rate, solid content, gel content and storage stability of the P(DV–BA–DE) miniemulsion were compared with those of the styrene-based P(St–BA–DAAM) emulsion. The results showed that the properties of the P(DV–BA–DE) miniemulsion were comparable to those of the P(St–BA–DAAM) emulsion in terms of the monomer conversion rate, solid content and gel content, and exhibited excellent storage stability. After employing the P(DV–BA–DE) miniemulsion as a leather coating, the air permeability and the tensile strength of the coated leather increased 2.14% and 11.71%, respectively. Furthermore, its antibacterial rates against E. coli (95.15%) and S. aureus (99.99%) were superior to those of the leather coated with the P(St–BA–DAAM) emulsion. The antibacterial mechanism proposed was based on the results of fluorescence confocal microscopy as well as SEM. Overall, this work not only provides new insights into the preparation of a novel, green, water-borne miniemulsion to substitute the styrene-based P(St–BA–DAAM) emulsion, but also provides a sustainable leather coating agent with excellent antibacterial properties, which has great significance for the sustainable development of the leather industry.